Asthma Control Test and Bronchial Challenge with Exercise in Pediatric Asthma - Tripodi, Salvatore; Barreto, Mario; Di Rienzo-Businco, Andrea; Grossi, Oriano; Sfika, Ifigenia; Ragusa, Giovanni; Campisano, Martina; Miceli-Sopo, Stefano (Frontiers in Pediatrics, 2016)
Background: Poor asthma control can lead to exercise-induced bronchoconstriction (EIB), but the relationship between subjective disease control and EIB is unclear. No studies have compared asthma control test (ACT) scores of children with those of their parents regarding EIB. We assessed whether ACT scores predict the occurrence of EIB in two age groups. We also evaluated ACT scores and objective measures as explanatory variables for airway response to exercise. Methods: Patients (71 aged <12 years, 93 aged ≥12 years) and their parents completed an ACT questionnaire separately. Current therapy, skin prick testing and spirometry at baseline and after exercise were assessed. EIB was defined as a fall in FEV1 of at least 12% from baseline. Sensitivity and specificity for cut-off values of ACT scores predictive of EIB were plotted, and the Area Under Curve (AUC) was described. Results: Atopy and current therapy were similarly frequent. EIB was observed in 23.9% of children aged <12 years and in 33.3% aged ≥12 years. EIB occurrence in subjects previously scored as having full control (25), partial control (20-24) and no control (<20) varied according to the age group and responder. Percentages of EIB cases increased as ACT scores decreased in children aged ≥12 years alone (child ACT scores, 25: 21.9%, 20-24: 31.1%, <20: 62.5%, p=0.017). Plots for ACT scores as predictors of EIB yielded low non-significant AUC values in children aged <12 years; by contrast, moderate AUC values emerged in children aged ≥12 years (child: 0.67, p=0.007; parent: 0.69, p=0.002). Sensitivity of ACT scores below 20 as a predictor of EIB was low in older children (child: 32.3%, parent: 22.6%), whereas specificity was high (child: 90.3%, parent: 93.5%). Multiple regression analysis with percent fall in FEV1 as dependent variable included FEV1/FVC%, ACT child score and gender in the prediction model ( r=0.42, p=0.000). Conclusion: ACT scores are a more effective means of excluding than confirming EIB in asthmatic patients aged ≥12 years; their predictive value decreases in younger patients. ACT scores together with lung function may help to predict airway response to exercise. New tools for pediatric asthma assessment may optimize this association.